THE INFLUENCE OF FACILITIES AND SERVICE QUALITY ON TRUST AND WORD-OF-MOUTH MARKETING AMONG RESIDENTS OF PUNCAK BUKIT GOLF SURABAYA APARTMENTS - Pribadi, Sergio; Sutanto, J.E. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research explores the development of apartments, particularly focusing on Puncak Bukit Golf Apartments in Surabaya, a popular choice for millennials due to limited land availability and rising property prices. However, the apartment complex has received numerous complaints regarding its facilities and quality, such as broken lifts, damaged gym equipment, and slow service. To address these issues, a pre-survey was conducted with 30 respondents, revealing significant concerns about these facilities. As a result, the researcher seeks to examine the impact of service quality and facilities on word-of-mouth marketing and trust. The objectives of this study include investigating the relationship between facilities and service quality, the effect of service quality on word-of-mouth marketing, the influence of facilities on word-of-mouth marketing, and how service quality mediates these relationships. Additionally, the study examines the impact of word-of-mouth marketing on trust. The research uses a sample of 170 respondents, aged 21 to 60 years, who have lived in the apartment for at least six months. Data will be collected via online questionnaires distributed through Google Forms, with purposive sampling employed. Data analysis will be conducted using Smart-PLS software. The results of the study are expected to show significant interconnections between all the variables.